What Middle Phalanx Base Fracture Characteristics are Most Reliable and Useful for Surgical Decision‐making?. Issue 12 (December 2015) - Janssen, Stein J.; Molleman, Jeroen; Guitton, Thierry G.; Ring, David
Abstract: Background: Fracture‐dislocations of the proximal interphalangeal joint are vexing because subluxation and articular damage can lead to arthrosis and the treatments are imperfect. Ideally, a surgeon could advise a patient, based on radiographs, when the risk of problems merits operative intervention, but it is unclear if middle phalanx base fracture characteristics are sufficiently reliable to be useful for surgical decision making. Questions/purposes: We evaluated (1) the degree of interobserver agreement as a function of fracture characteristics, (2) the differences in interobserver agreement between experienced and less‐experienced hand surgeons, and (3) what fracture characteristics and surgeon characteristics were associated with the decision for operative treatment. Methods: Ninety‐nine (33%) of 296 hand surgeons evaluated 21 intraarticular middle phalanx base fractures on lateral radiographs. Eighty‐one surgeons (82%) were in academic practice and 57 (58%) had less than 10 years experience. Participants assessed six fracture characteristics and recommended treatment (nonoperative or operative: extension block pinning, external fixation, open reduction and internal fixation, volar plate arthroplasty, or hemihamate autograft arthroplasty) for all cases. Results: With all surgeons pooled together, the interobserver agreement for fracture characteristics was substantial for assessment of a 2‐mm articular step or gap (kappa, 0.73; 95% CI, 0.60‐0.86; p < 0.001), subluxation or dislocation (kappa, 0.72; 95% CI, 0.58‐0.86; p < 0.001), and percentage of articular surface involved (intraclass correlation coefficient [ICC], 0.67; 95% CI, 0.54‐0.81; p < 0.001); moderate for comminution (kappa, 0.55; 95% CI, 0.39‐0.70; p < 0.001) and stability (kappa, 0.54; 95% CI, 0.39‐0.69; p < 0.001); and fair for the number of fracture fragments (ICC, 0.39; 95% CI, 0.27‐0.57; p < 0.001). When recommending treatment, interobserver agreement was substantial (kappa, 0.69; 95% CI, 0.50‐0.88; p < 0.001) for the recommendation to operate or not to operate, but only fair (kappa, 0.34; 95% CI, 0.21‐0.47; p < 0.001) for the specific type of treatment, indicating variation in operative techniques. There were no differences in agreement for any of the fracture characteristics or treatment preference between less‐experienced and more‐experienced surgeons, although statistical power on this comparison was low. None of the surgeon characteristics was associated with the decision for operative treatment, whereas all fracture characteristics were, except for stable and uncertain joint stability. Articular step or gap (β, 0.90; R‐squared, 0.89; 95% CI, 0.75‐1.05; p < 0.001), likelihood of subluxation or dislocation (β, 0.80; R‐squared, 0.76; 95% CI, 0.59‐1.02; p < 0.001), and unstable fractures (β, 0.88; R‐squared, 0.81; 95% CI, 0.67‐1.1; p < 0.001), are most strongly associated with the decision for operative treatment. Conclusions: We found that assessment of a step or gap and likelihood of subluxation were most reliable and are strongly associated with the decision for operative treatment. Surgeons largely agree on which fractures might benefit from surgery, and the variation seems to be with the operative technique. Efforts at improving the care of these fractures should focus on the comparative effectiveness of the various operative treatment options. Level of Evidence: Level III, diagnostic study.